Output, stock markets and macro-policy measures in a Keynesian portfolio model - Toichiro Asada; Matthieu Charpe; Peter Flaschel; Christopher Malikane; Tarik Mouakil; Christian R. Proa\~no (Intervention. European Journal of Economics and Economic Policies, 2011)
We present a simple macrodynamic model of the real-financial markets inter action with a dynamic multiplier representing the goods market and a structured portfolio choice between money holdings and equities. This is contrasted with Blanchard's (1981) alternative approach, where interest-bearing bonds and equities are perfect substitutes and are subject to myopic perfect foresight, with the result that the usual saddle-point dynamics is established, and where therefore the jump-variable technique of the rational expectations approach is needed in order to tame the explosive nature of the model by assumption. We consider this latter representation a very virtual one in contrast to our descriptive treatment of the interaction of the real with the financial markets.Our implied dynamical system has three dimensions: output, share prices and capital gains expectations. We show that this model exhibits a financial accelerator mechanism that endangers the stability of its stationary solution, at least when it becomes sufficiently strong. Furthermore, we show that this type of instability can definitely be overcome if actual capital gains are taxed to a sufficient degree. This tax policy is therefore effective as compared to an interest rate policy of Taylor type, showing that monetary policy may not impact the markets for risky financial assets, unless it is interpreted as state of confidence for the current situation of the economy and may therefore be fairly overrated in the current macrodynamic literature. By contrast, all policy measures that stabilise the profit rate of the economy may add to the stability implications of the assumed Asada et al. (2010) type tax on capital gains.
Keywords: E12; E32; 330; portfolio choice; financial accelerators; fiscal policy; monetary policy